TANGGAPAN SISWA TERHADAP PENGGUNAAN STRATEGI PEMBELAJARAN MULTIPLE INTELLIGENCES (MI) HUBUNGANNYA DENGAN MOTIVASI BELAJAR PADA MATA PELAJARAN SKI - Fitriani, Risda Davila (ATTA`DIB, 2015)
The aim of research is to know about student reaction for using multiple intelligences strategies connection with student motivates on SKI lesson at class VI. This research consists of two variables, student reaction for using multiple intelligences as variable X and student motivates on SKI lesson as variable Y. This research is quantitative use descriptive method with Datacollecting instrument shaped observation in class with a teacher and head master to get some information about system in the school and questionnaires. For sample and population use totally sample technique with 37 respondent. Data analyze with correlation statistics. Correlation coefficient use rank spearman correlation because two variables distribution is abnormal. From Data analyze get know variable X has value is 4,35 classified good/high while variable Y has value 3,90 classified good/high. Connection between two variable can appoint with correlation figure is 0,995 to show up this correlation are very good/very high and calculation result with t test is 58,9 from significantion standard 5 % is 2,0315 from result db 35. This is show means there is correlation between variable X and variable Y. Based on calculation correlation value and effect test variable X to variable Y get value K is 0,1 result effect is 90 %. Its means variable Y get effect variable X is 90 % and 10 % again from effect other factor.